Heat transfer in couple stress Williamson hybrid nanofluid with slip viscous dissipation and radiation and slip impacts: Semi-numerical simulation - Rehman, Ali; İnç, Mustafa; Mohammad, Alsharef; Jan, Rashid (World Scientific Publ Co Pte Ltd, 2025)
Hybrid nanofluids (HNFs) are better at transferring heat than single-component nanofluids and even common fluids like water, oil, and ethylene glycol. HNF is the combination of metal and metal oxide nanoparticles that maximize thermal characteristics and enhance heat dissipation. In heat exchangers, HNFs increase the heat transfer coefficient, enabling more efficient and compact designs. In the chemical processing, refrigeration, and power plant sectors, this is essential. This study looks at how heat moves through a couple-stress Williamson HNF flow, taking into account the effects of slip boundary conditions (BCs), viscous dissipation, and the mutual inspiration of thermal radiation. We use the boundary layer and conservation principles to come up with the nonlinear governing equations. Then, we use the right similarity transformations to turn them into a form with no dimensions. We use the semi-numerical method HAM to solve the system of nonlinear equations. The radiation parameter, slip velocity, Eckert number, WP, nanoparticle volume fraction, porosity parameter, and couple stress parameter are just some of the important things that this in-depth study looks at in terms of how they affect the speed and temperature fields. Tables and graphical representations illustrate the skin friction coefficient and NN. According to the results, slip conditions dramatically change the temperature (TP) and velocity profile (VP), although radiation effects and viscous dissipation improve heat transport in the fluid. This paper's primary goal is to solve the current flow problem, with the hope that the results will help other scholars or researchers. This work helps us learn more about how non-Newtonian fluids behave thermally in complex flow situations. It could be used in thermal engineering systems, polymer processing, and lubrication.
Keywords: Permeable shrinking surface; TiO2, Ag; hybrid nanofluid; HAM; 2D problem